POTENSIAL PELANGGARAN HUKUM PERSAINGAN PADA TATA NIAGA GULA - Ari Purwadi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
As a public policy instruments, implementation of sugar import commerce system should subject to fulfilling society needs especially customers, such as sugar cane farmers and sugar factories. The potential law violent towards cartel and oligopoly is based on